The microbiota–gut–brain axis: A promising avenue to foster healthy developmental outcomes. Issue 5 (14th January 2019) - Brett, Bonnie E.; de Weerth, Carolina
Abstract: Fostering healthy developmental growth in the first years of life is associated with numerous favorable cognitive, social, and economic outcomes. Funding and promoting research aimed at identifying potential targets for early intervention should be a top priority for lawmakers and funders. One promising avenue of research and potential early intervention is the microbiota–gut–brain axis. In this report, we briefly examine the role of the gut microbiota in human life, focusing on links with health, cognition, and behavior. We then discuss the development of the gut microbiota and the critical early window in which colonization occurs. Then, we review current nonnutritive means of influencing the gut microbiota in early life. Finally, we discuss the implications this work has for early intervention in low‐income communities and end with recommendations regarding further research and research funding priorities.